2008
DOI: 10.1542/peds.2007-3811
|View full text |Cite
|
Sign up to set email alerts
|

In-Hospital Falls of Newborn Infants: Data From a Multihospital Health Care System

Abstract: If the incidence of a neonatal in-hospital fall in this study is representative, then 600 to 700 such falls occur annually in the United States. Relatively few scenarios explain the majority of falls. We speculate that the prevalence of this error could be reduced significantly by enacting programs aimed at eliminating or monitoring the most common circumstances under which these falls occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(92 citation statements)
references
References 15 publications
2
84
0
4
Order By: Relevance
“…67 The Oregon Patient Safety Review evaluated 7 hospitals that were part of 1 larger health system and identified 9 cases of newborn falls (from 22 866 births), for a rate of 3.94 falls per 10 000 births over a 2-year period from 2006 to 2007, which is higher than previous reports of 1.6 per 100 000. [68][69][70] It is not clear whether this higher incidence was attributable to an actual increase or better reporting. For hospitals transitioning to mother-infant dyad care (1 nurse providing care for both mother and infant) or separate mothernewborn care while rooming-in, it is important to communicate to staff that the same level of attention and care is necessary to provide optimal safety.…”
Section: Safety Concerns Regarding Rooming-inmentioning
confidence: 98%
“…67 The Oregon Patient Safety Review evaluated 7 hospitals that were part of 1 larger health system and identified 9 cases of newborn falls (from 22 866 births), for a rate of 3.94 falls per 10 000 births over a 2-year period from 2006 to 2007, which is higher than previous reports of 1.6 per 100 000. [68][69][70] It is not clear whether this higher incidence was attributable to an actual increase or better reporting. For hospitals transitioning to mother-infant dyad care (1 nurse providing care for both mother and infant) or separate mothernewborn care while rooming-in, it is important to communicate to staff that the same level of attention and care is necessary to provide optimal safety.…”
Section: Safety Concerns Regarding Rooming-inmentioning
confidence: 98%
“…Estudos que tratam desse tema são raros e não foi encontrado na literatura nacional dados sobre frequência de queda na área neonatal em ambiente hospitalar. Nos Estados Unidos da América (EUA), um estudo (25) realizado em 18 hospitais de uma rede de serviço de saúde no período de 2004 a 2006, analisou a ocorrência de 14 quedas, tendo uma incidência estimada de 1,6 quedas por 10.000 nascidos vivos. Em Oregon, EUA (8) em sete hospitais foram observados nove casos de quedas de RN de 2006 a 2007, significando uma taxa de 3,94 quedas para 10.000 nascimentos.…”
Section: Discussionunclassified
“…As consequências para os RN associadas às quedas, encontradas em outros estudos (8,25) , abrangem desde nenhum ferimento, lesão menor como contusão, até lesões mais graves como traumatismo. Um estudo (2) menciona que não houve morte de RN resultante de queda no ambiente hospitalar, mas efeitos emocionais e psicológicos como a ansiedade e preocupação excessiva nas famílias decorrentes de quedas de bebês.…”
Section: Discussionunclassified
“…Falling incidents are particularly encountered at overcrowded delivery and education hospitals, and trauma incidents resulting from falling occur but unfortunately not put on the record. There are a limited number of publications in the literature regarding traumas resulting from in-hospital falls of newborns but there is no scale evaluating the risks and risk reduction measures [13]. In a previous study, 14 trauma cases were reported among 888774 deliveries.…”
Section: Introductionmentioning
confidence: 99%
“…No deaths were reported. One patient sustained a depressed skull fracture and was transported to the regional children's hospital [1]. …”
Section: Introductionmentioning
confidence: 99%